The linkage between green banking practices and green loyalty: A customer perspective - Deepthi S. Pawar; Jothi Munuswamy (Banks and Bank Systems, 2022)
The aim of this study is to explore the bank customers’ perceptions towards green banking practices. This study uses a convenient sampling method. Pre-tested questionnaires were employed to collect data. The data were collected conveniently from 358 bank customers. However, the final sample includes 304 responses after ignoring null responses (n = 304). The Structural equation modeling (SEM) was applied for the analyses. The significant results of the study indicate that green banking practices positively influence green image (p = 0.001) and green trust (p = 0.025), while it does not significantly affect green loyalty (p = 0.642). The mediation analysis reveals that green image mediates the relationship between green banking practices and green loyalty, while green trust does not mediate the relationship between the same. The results have practical implications for banking institutions in India to recognize the importance of environmental initiatives in influencing the decisions of bank customers.